COVID-19 Infection in Pregnancy Increases Length of Hospitalization and Need for Postpartum Intermediate Care - Slamet Susanto; Zulvayanti Zulvayanti; Windi Nurdiawan; Djamhoer Martaadisoebrata; Hadi Susiarno (Indonesian Journal of Obstetrics & Gynecology Science, 2023)
Objective: To find the prevalence and the outcomes of pregnant women with COVID-19 infection. Method: This was a cross-sectional study. The subjects were selected by total sampling. All pregnant women with COVID-19 infection and without COVID-19 infection who gave birth at Harapan Mulia Hospital from June 1, 2020 to August 31, 2021 with complete medical record data were recruited.Results: The average age of the patients with COVID-19 was 29.10 ± 7.325 years and the average age of the patients without COVID-19 was 29.24 ± 7.021 years. The average gestational age of pregnant women with COVID-19 was 37.52 ± 1.978 weeks and without COVID-19 was 38.14 ± 1.718 weeks. From the results of the statistical test of maternal outcomes, it was obtained that the P value for the length of hospitalization and type of treatment room after delivery was < 0.05, while the other variables were >0.05. For perinatal outcome analysis, from the results of statistical tests, it was obtained that P values for all variables were >0.05. Conclusion: There are differences in maternal outcomes and no differences in perinatal outcomes between pregnant women with COVID-19 and pregnant women without COVID-19 infection.Infeksi COVID-19 pada Kehamilan Meningkatkan Lama Rawat Inap dan Kebutuhan Ruang Intermediate Pasca PersalinanAbstrakTujuan: Mengetahui besarnya prevalensi dari ibu hamil dengan infeksi COVID-19 serta luarannya di RS Harapan Mulia BekasiMetode: analitik cross-sectionalHasil: Perbandingan demografi kelompok Ibu hamil dengan COVID-19, rata-rata usia pasien adalah 29,10 ± 7,325 tahun dan non COVID-19 29,24 ± 7,021 tahun. Rata-rata usia kehamilan ibu hamil dengan COVID-19 adalah 37,52 ± 1,978 minggu dan non COVID-19 adalah 38,14 ± 1,718 minggu. Dari hasil uji statistik luaran maternal, diperoleh nilai P pada lama perawatan dan jenis perawatan setelah persalinan lebih kecil dari 0,05 (nilai p < 0,05), sementara variabel lainnya lebih besar dari 0,05 (nilai p>0,05). Untuk analisis luaran perinatal, dari hasil uji statistik diperoleh nilai P pada semua variabel lebih besar dari 0,05 (nilai  >0,05). Kesimpulan: Terdapat perbedaan luaran maternal dan tidak didapatkan perbedaan luaran perinatal antara kelompok ibu hamil dengan COVID-19 dan non COVID-19.Kata kunci: infeksi COVID-19, luaran maternal, luaran perinatal